The Role of Emotion Regulation Difficulties in the Relation Between PTSD Symptoms and the Learned Association Between Trauma-Related and Cocaine Cues. (23rd August 2016) - Tull, Matthew T.; Gratz, Kim L.; McDermott, Michael J.; Bordieri, Michael J.; Daughters, Stacey B.; Lejuez, Carl W.
ABSTRACT: Background : PTSD and cocaine dependence frequently co-occur. However, few studies have specifically examined the functional relation between trauma-related distress and cocaine use and none have examined the extent to which PTSD is associated with a learned association between trauma cues and cocaine or the underlying role of emotion regulation difficulties in this relation. Objectives : Thus, this study used a novel version of the Implicit Association Test (IAT) to examine the relation of PTSD symptoms to the strength of the trauma-cocaine cue association and the role of specific emotion regulation difficulties in this relation. Methods : A sample of 42 cocaine-dependent inpatients with a history of interpersonal traumatic exposure were recruited. Participants completed a series of questionnaires assessing PTSD symptom severity and emotion regulation difficulties. Participants then completed the IAT. Results : Results revealed a significant indirect relation of PTSD symptom severity to the strength of the trauma-cocaine cue association through the specific emotion regulation dimension of difficulties controlling impulsive behaviors when distressed. Conclusion/Importance : Results build upon extant research suggesting that factors related to emotional responding and regulation may underlie the relation between trauma-cue exposure and responses to cocaine cues among cocaine dependent patients with PTSD. The finding that PTSD symptom severity is associated with the strength of the trauma-cocaine cue association through one particular dimension of emotion regulation difficulties, difficulties controlling impulsive behaviors when distressed, highlight the potential utility of interventions focused on improving emotion regulation and impulse control abilities among trauma-exposed cocaine dependent patients.